Proceedings of the International Conference on Science and Technology (ICOSAT 2017) 2018
DOI: 10.2991/icosat-17.2018.32
|View full text |Cite
|
Sign up to set email alerts
|

Effective IT Governance in Higher Education Institutions: The Conceptual Model

Abstract: Recently, a considerable literature has grown up around the theme of Information Technology Governance (ITG) in the organization. While some research has been carry out on ITG in general, there is still very little scientific understanding of Effective ITG in the context of Higher Education Institutions (HEI). To gain the effectiveness of IT governance in HEIs need to follow the IT governance mechanisms that provide the set of process and procedures which is in line with the strategic alignment between IT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Investigation verifies that perhaps the template will guarantee that data centers are accessed anonymously by consumers and also that cloud providers efficiently determine the reputation of users thereby infringing consumer privacy. [25] addressed and offers the efficient assessment model of IT administration that could be used in specific, by organizational management throughout the HEI. In addition, this research identifies the variables that lead to successful IT accomplish a specific objective upon that domain's published studies.…”
Section: Preliminariesmentioning
confidence: 99%
“…Investigation verifies that perhaps the template will guarantee that data centers are accessed anonymously by consumers and also that cloud providers efficiently determine the reputation of users thereby infringing consumer privacy. [25] addressed and offers the efficient assessment model of IT administration that could be used in specific, by organizational management throughout the HEI. In addition, this research identifies the variables that lead to successful IT accomplish a specific objective upon that domain's published studies.…”
Section: Preliminariesmentioning
confidence: 99%
“…1. Model penelitian merupakan adopsi dari model evaluasi tata kelola TI yang digunakan oleh pada organisasi di lembaga pendidikan tinggi (HEI) [22]. Pada model ini diidentifikasi faktor-faktor mekanisme tata kelola teknologi informasi (TI) yang berkontribusi pada efektifitas tata kelola teknologi informasi (TI) .yaitu: Komisi pengarah TI, keterlibatan senior manager TI, sistem pengukuran kinerja organisasi dan sistem komunikasi organisaasi.…”
Section: P-issn: 2086 -4981unclassified
“…Menshawy et al (2022) argue that implementing formal IT governance practices at the management level can offer significant benefits and enhance performance while ensuring strategic alignment, a point also supported by Huygh and De Haes (2016). Huda et al, (2017); Merchan-Lima et al (2021) recommend establishing an IT governance framework that includes an effective structure, processes and relational mechanisms. However, Khouja et al (2018); Jairak et al (2015) highlight that research on the adoption of IT governance in universities is less common than in the business sector, with only 17% of studies focusing on universities, as indicated by Tjong et al (2017).…”
Section: Introductionmentioning
confidence: 98%